The study about determining the reliability of operations management, risk warning and opportunity of repair risk - zhe, yin (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
In this paper, how to transform operations management and supply chain management, industrial engineering problems, project management, and other issues into a complex system reliability problem has been provided. It become possible that reliability of users demand is determined first and opportunity of choosing the repair the risk. This paper can provide a theoretical basis for research on related issues, which has a certain value.